In Silico ADMET Studies, Molecular Docking and Molecular Dynamics Simulation of Thiadiazole Derivatives for the Identification of Putative HsaA Monooxygenase Inhibitors - Zheng, Min; Kumar, Ankush; Vishakha; Behl, Tapan; Rawat, Ravi; Wal, Pranay; Rani, Ketki; Agarwal, Mohit; Waghmode, Raghwendra R.; Gulati, Monica; Khan, Azmat Ali; Alanazi, Amer M.; et al. (Current Medicinal Chemistry, 2025)
<span class=
Keywords: binding affinity